2018
DOI: 10.1016/j.vaccine.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines, inspiring innovation in health

Abstract: This report covers the topics of pandemics, epidemics and partnerships, including regulatory convergence initiatives, new technologies and novel vaccines, discussed by leading public and private sector stakeholders at the 18th Annual General Meeting (AGM) of the Developing Countries Vaccine Manufacturers’ Network (DCVMN). Contributions of Gavi and the vaccine industry from emerging countries to the growing global vaccine market, by improving the supply base from manufacturers in developing countries and contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Vaccines are powerful tools for controlling pandemic respiratory viruses [ 73 ]. In December 2020, two vaccines containing messenger RNA encoding the SARS-CoV-2 spike protein (mRNA-1273 (Moderna) and BNT162b2 (Pfizer/BioNTech)) were authorized for emergency use in many countries based on promising efficacy data from phase III trials in immunocompetent adults [ 74 , 75 ].…”
Section: Vaccinesmentioning
confidence: 99%
“…Vaccines are powerful tools for controlling pandemic respiratory viruses [ 73 ]. In December 2020, two vaccines containing messenger RNA encoding the SARS-CoV-2 spike protein (mRNA-1273 (Moderna) and BNT162b2 (Pfizer/BioNTech)) were authorized for emergency use in many countries based on promising efficacy data from phase III trials in immunocompetent adults [ 74 , 75 ].…”
Section: Vaccinesmentioning
confidence: 99%
“…The findings from this scoping review further suggest that the ability of a country to implement a mass vaccination programme is an important factor that may influence equitable access 23. Vaccination programmes are resource intensive; therefore, to maximise the benefit of COVID-19 vaccines and reduce waste due to improper implementation, it has been suggested that allocation frameworks should consider a country’s ability to vaccinate 1 13 23 24 27 52 62 63. Most LMICs have well-structured immunisation programmes for polio, measles, smallpox, etc, facilitated by organisations such as UNICEF and Gavi, which could support a large-scale pandemic vaccination programme.…”
Section: Resultsmentioning
confidence: 91%
“…For example, preformed plastic vials are being successfully used for oral rotavirus and cholera vaccines. 62 Data solutions should also be considered, as these could support alternative vaccine delivery systems for target groups, as well as being an important tool to capture the populations' vaccination history. 28 Smooth regulatory and market authorisation processes for vaccines can facilitate the distribution of vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing attention to new packaging technologies including blow-fill-seal (BFS) tube technology, multi-component containers and smart packaging, while intradermal delivery devices, microarray patches (MAPs) and sublingual delivery represent new delivery technologies [7] . BFS technology used for inactivated cholera vaccine has reduced package volume by 30% and shipping weight by over 50%, improving storage, transportation and waste management [8] . Direct participation in the vaccine supply chain may help countries address the constraints existing in vaccine supply chains through assessing the need for new structures and policies and applying system design techniques [9] .…”
Section: Methodsmentioning
confidence: 99%